PERANCANGAN PROSES MANUFAKTUR SHOCK ABSORBER DENGAN MENGGUNAKAN MEDAN ELEKTROMAGNET SEBAGAI MEDIUM PEREDAM - Fariz Hilman Fauzan, (2021)
This research was conducted to determine the design and manufacturing process of shock absorbers that use an electromagnetic field as a damping medium, where this electromagnetic field is used as a substitute for the damping medium in shock absorbers which usually have a liquid or gas dampening medium. The research was carried out by designing 2D and 3D shock absorbers, then from this 2D and 3D dimensional design the design of the shock absorber manufacturing process was carried out from raw materials to finished materials, after designing the manufacturing process and then designing the shock absorbers a simulation process was carried out to determine the effect of the field electromagnet as damping medium. The results of this study determine the 2D and 3D designs of electromagnetic shock absorbers and know the design of the manufacturing process of these shock absorbers, and based on the simulations carried out on the shock absorbers it is known the influence of the electromagnetic field as the damping medium.